Spontaneous recovery of memory functions in an untreated case of anti NMDAR encephalitis – a reason to maintain hope. Issue 1 (2nd January 2017) - McIvor, Katherine; Moore, Perry
Abstract: Objective: Anti N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis is an autoimmune disorder that was only fully discovered recently and neuropsychological outcome data remains sparse. We present the case of BA, a 19-year-old male, which illustrates the cognitive outcome in an untreated case over a time period of over 2½ years.Method: We conducted three cognitive assessments, including tests of memory and executive functioning, over this time period and considered the evidence for reliable change in memory function using the Wechsler Advanced Clinical Solutions (ACS) serial assessment package.Results: Our findings revealed mild memory problems 6 months post-discharge with, at best, static and potentially declining memory functioning at follow-up assessment 12 months post-discharge. However, the results of testing at 30 months post-discharge revealed significant improvements in immediate and delayed memory index performances.Conclusions: Our report of a case of anti-NMDAR encephalitis provides evidence for spontaneous improvements in memory functioning occurring more than 2 years after initial assessment and also demonstrates both the utility and potential limitations of the ACS serial assessment software when used in a relatively typical clinical assessment situation.